Valve-in-valve procedures for degenerated surgical and transcatheter aortic valve bioprostheses using a latest-generation self-expanding intra-annular transcatheter heart valve - Schaefer, Andreas; Demal, Till Joscha; Bhadra, Oliver D.; Grundmann, David; Voigtländer, Lisa; Waldschmidt, Lara; Schirmer, Johannes; Pecha, Simon; Schneeberger, Yvonne; Schofer, Niklas; Sörensen, Nils; Blankenberg, Stefan; et al. (Frontiers in Cardiovascular Medicine, 2023)
Background: Valve-in-valve (ViV) transfemoral (TF) transcatheter aortic valve implantation (TAVI) for failing aortic surgical bioprostheses or transcatheter heart valves (THV) has demonstrated reasonable clinical and hemodynamic efficacy. Traditionally, self-expanding (SE) supra-annular THV are considered to result in superior hemodynamics compared to balloon-expandable (BE) intra-annular THV after ViV. However, so far there is no data on latest generation intra-annular SE THV for aortic ViV procedures which might be superior with regard to coronary access or subsequent valve reintervention.We herein aimed to evaluate a latest generation SE intra-annular THV for aortic ViV procedures.: Between May 05/2022 and November 11/2022, 5 consecutive patients (4/5 female, mean age 76.2 years, mean STS PROM Score 2.9%) received ViV TAVI using the Navitor system (Abbott, Chicago, IL, US) for treatment of failing surgical bioprostheses or THV. Data were retrospectively analyzed according to updated Valve Academic Research Consortium (VARC-3) definitions.Results: At 30 days absence of mortality and VARC-3 adjudicated clinical endpoints was documented. Echocardiography at 30 days revealed complete absence of PVL and single digit mean transvalvular gradients (mean 6.0 mmHg) in all cases.The investigated intra-annular SE-THV results in excellent 30-day outcomes for aortic ViV procedures for failing surgical bioprostheses or THV. Despite the intra-annular design, hemodynamic results were excellent, even in small bioprostheses. Ease of use of this valve platform is reflected by only two cycles of resheathing in 5 ViV procedures with hemodynamic stability during all steps of valve deployment.